Comparison of Clinical and Laboratory Characteristics Between Surgically and Non-Surgically Treated Multiple Myeloma Patients with Spinal Involvement - Gültekin Baş; Fatih Sağlam; Abdulvahap Aslan (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
This study aimed to compare the clinical, demographic, and laboratory characteristics of multiple myeloma patients with spinal involvement who underwent surgical versus non-surgical management.This retrospective, single-center cohort study included 46 multıple myeloma patients with radiologically confirmed spinal involvement who were treated at Private Ümit Hospital between 2013 and 2025. Eighteen patients underwent surgical intervention, while 28 were managed medically. Demographic data, presenting symptoms, and laboratory parameters were compared between groups. Data were analyzed using SPSS 25.0. Normality was assessed by the Shapiro–Wilk test, and appropriate statistical tests (Student’s t-test, Mann–Whitney U, chi-square) were applied. The mean age was 63.3 ± 6.0 years in the surgical group and 67.3 ± 8.7 years in the non-surgical group. Back or low back pain was the most frequent presenting symptom in surgically treated patients, while systemic manifestations such as fatigue, weight loss, and diffuse musculoskeletal pain predominated in the non-surgical group. Laboratory comparisons revealed significantly higher BUN (p = 0.025), beta-2 microglobulin (p = 0.008), and ISS scores (p = 0.034) in the non-surgical cohort, indicating a greater systemic disease burden. No significant intergroup differences were observed in other biochemical parameters. Multiple myeloma patients with spinal involvement who undergo surgery tend to have lower systemic disease activity and better renal function compared to those treated conservatively. The presence of neurological or pain symptoms due to proximity to neural structures may lead to earlier diagnosis in these patients.